Laparoscopic partial nephrectomy following tumor embolization in a hybrid room. Feasibility and clinical outcomes. (December 2017) - Panayotopoulos, Paul; Bouvier, Antoine; Besnier, Louis; Rousselet, Marie Christine; Nedelcu, Cosmina; Baize, Nathalie; Beydon, Laurent; Aubé, Christophe; Azzouzi, Abdel-Rahmène; Bigot, Pierre
Abstract: Purpose: In order to limit ischemia and operative bleeding during and after partial nephrectomy we developed a clampless laparoscopic technique, in a hybrid operating room, immediately after super-selective arterial embolization of the renal tumor. We evaluated feasibility and morbidity of this new approach of zero ischemia in partial nephrectomy. Methods: We included prospectively 50 consecutive patients treated in a hybrid operating room by this new technique for a localized renal tumor in a university hospital between May 2015 and January 2017. We evaluated perioperative data, postoperative complications, surgical margin and modification of renal function one month after surgery. Renal tumor complexity was evaluated by the R.E.N.A.L. score. Results: We included 30 (60%) men and 20 (40%) women with a median age of 61 years (32–84) and a median BMI of 26.85 kg/m 2 (20.1–46.4). Tumors were at low, median and high complexity in respectively 11 (22%), 32 (64%) and 7 (14%) cases. Median endovascular and surgical procedures durations were 43 min (16–120) and 80 min (32–150). Median blood loss was 100 mL (10–850). Two Clavien II complications occurred. Median length of hospital stay was 3 days (2–7). Renal function was not modified one month after partial nephrectomy. Median tumor size was 3 cm (1.2–8). Forty tumors (80%) were malignant and surgical margins were positive in one (2%). Conclusions: Clampless laparoscopic partial nephrectomy in a hybrid operating room without pedicular dissection after previous tumoral embolization is a technically safe and carcinologically efficient mini-invasive alternative for the management of localized renal tumors. Highlights: Using a hybrid operating room, laparoscopic partial nephrectomy was performed immediately after selective tumor embolization. No major complication occurred. Blood loss was limited. Median hospital stay was 3 days. After 6 months follow-up, there was no significant change of renal function. This nephron-sparing surgery is a technically safe and carcinologically efficient mini-invasive alternative for the management of localized renal tumors.